Evidence of Intramolecular Structural Stabilization in Light Activated State of Orange Carotenoid Protein - McKinney, J. A.; Sharma, A.; Crossen, K.; Deng, Y.; George, D. K.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. G. (Biophysical Journal, 2020)
Orange carotenoid protein (OCP) controls efficiency of the light harvesting antenna, the phycobilisome (PBS), in diverse cyanobacteria and prevents oxidative damage. It is the only known photoactive protein that uses a carotenoid, canthaxanthin, as its chromophore. The structure of OCP consists of two globular domains, connected by an unstructured loop, that forms a hydrophobic pocket for the carotenoid. In low light, canthaxanthin bound OCP is inactive and appears orange. Illumination by strong light results in an active state that interacts with the PBS to induce fluorescence quenching, a red appearance and conformational changes that include a 12Å shift by canthaxanthin into the N-terminal domain. Terahertz (THz) dynamical transition measurements and anisotropic terahertz microscopy are used to measure the intramolecular structural dynamics in the inactive and active states, which can be induced by photoexcitation or chaotropic salts. The measurements indicate that the active state has a decrease in structural flexibility, which may be related to enhanced interactions with the PBS.
ISI Document Delivery No.: KK8YX Times Cited: 0 Cited Reference Count: 0 McKinney, Jeffrey A. Sharma, Akansha Crossen, Kimberly Deng, Yanting George, Deepu K. Lechno-Yossef, Sigal Kerfeld, Cheryl Markelz, Andrea G. 64th Annual Meeting of the Biophysical-Society Feb 15-19, 2020 San Diego, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIH STTRUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [R41 GM125486] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486. 1 2 Cell press Cambridge 1542-0086
Keywords: Biophysics

Stabilization of Terahertz Vibrational Modes in Illuminated Orange Carotenoid Protein Crystals - McKinney, J.; Sharma, A.; Deng, Y.; George, D.; Lechno-Yossef, S.; Kerfeld, C.; Markelz, A. (2020 45th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz), 2020)
Orange carotenoid protein (OCP) controls efficiency of the phycobilisome (PBS), the light harvesting antenna in cyanobacteria, to prevent oxidative damage. The OCP switches from resting state to photo protective state with intense blue light illumination. Questions persist as to why OCPR interaction increases with the PBS over that with the OCPO. Here we examine the role of long-range intramolecular vibrations within OCP. Using Stationary Sample Anisotropic Terahertz Microscopy (SSATM) we measure changes in the intramolecular vibrations with photo switching. We report the first observation of switching in the intramolecular vibrations with photoexcitation. Results suggest that there is a stiffening of the molecule in the photo protective state. This increase in structural stability may enhance the interaction with the PBS change in OCP interaction with PBS. In low light, carotenoid bound OCP appears orange (OCP o ) and is inactive. Illumination by strong light converts OCP to the active, red (OCPR) state, which interacts with the PBS. A comparison of anisotropic THz microscopy measurements of dark adapted (OCP o ) and illuminated OCP crystals indicate differences in their vibrational modes that may be important for OCP-PBS interactions.

THz Transmission through Submillimeter Apertures - LaFave, T.; Lee, A.; Kao, T.-Y.; Markelz, A. (IRMMW-THz, 2020)
Terahertz near-field microspectroscopy is emerging as an essential tool for characterization of novel materials and biomolecules. It is important to ensure the near field geometry used does not introduce spectral artifacts. For example, many scanning techniques can be strongly influenced by the interaction between the scattering tip and the sample. Here we examine the spectroscopic effects of a 200 μm diameter aperture for THz near-field measurements. We use HFSS to model free-space transmission through samples with resonant absorbance as a function of sample thickness, lateral sample width, and aperture diameter. We examine the transmitted power and spectral fidelity for coupling of transmitted THz light onto a detector. These studies inform corrective post-measurement analysis algorithms and design of near-field detection systems.

Stationary Sample Anisotropic THz Spectroscopy using Discretely Tunable THz Sources - LaFave, T., Jr.; George, D. K.; Markelz, A. G.; McNee, Ian; Kozlov, Vladimir; Schunemann, Peter (2019 44th International Conference on Infrared, Millimeter, and Terahertz Waves, 2019)
We demonstrate anisotropic THz spectroscopy of sucrose using newly developed compact discretely tunable THz sources for turn-key spectroscopic systems.
Irmmw-thz 44th International Conference on Infrared, Millimeter, and Terahertz Waves (IRMMW-THz) Sep 01-06, 2019 Paris, FRANCE Lytid; TYDEX; Swiss Terahertz; Fondat Maison Chimie; CNRS, Lab Physique ENS; Li2S; LUNA; MenloSystems; ENS; PSL Univ Paris; FYLA; ADVANTEST; Springer Nature; Soc Francaise Physique; Sorbonne Univ; Int Soc Infrared Millimeter & Terahertz Waves; IEEE; GDR NANO THz MIR 2162-2027

Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
ISI Document Delivery No.: BN5PJ Times Cited: 0 Cited Reference Count: 17 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Lee Y. S., 2006, APPL PHYS LETT, V89 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Lin A., 2013, ANTIPHASE DOMAIN ANN Niessen K. A., BIOPHYSICAL J, V112, P933 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 PARSONS DF, 1971, APPL OPTICS, V10, P1683 Singh R., 2013, PHYSICS Strachan CJ, 2005, J PHARM SCI-US, V94, P837, DOI 10.1002/jps.20281 Tassev V., 2013, SPIE LASE, V9 Tekavec P., 2017, FRONTIERS OPTICS 201 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Walther M, 2003, CHEM PHYS, V288, P261, DOI 10.1016/S0301-0104(03)00031-4 Zeitler JA, 2009, EUR J PHARM BIOPHARM, V71, P2, DOI 10.1016/j.ejpb.2008.08.012 George, D. K. LaFave, T. J. Markelz, A. G. Mcnee, Ian Tekavec, Patrick Kozlov, Vladimir Schunemann, Peter LaFave, Tim/0000-0003-2925-8657 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41GM125486] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41 GM125486] Funding Source: Medline 0277-786x 1098311
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
ISI Document Delivery No.: GD5RB Times Cited: 1 Cited Reference Count: 0 Deng, Yanting Luck, Catherine H. Romo, Tod D. Grossfield, Alan M. Bandara, Sepalika Ren, Zhong Yang, Xiaojing Markelz, Andrea G. 62nd Annual Meeting of the Biophysical-Society Feb 17-21, 2018 San Francisco, CA Biophys Soc 1 7 Cell press Cambridge 1542-0086
Keywords: Biophysics

Investigation of the Isotope Shift in Protein Collective Vibrations - Luck, C.; Xu, M.; Markelz, A. (APS 2018, 2018)

Measuring Protein Intramolecular Dynamics with Terahertz Light: Functional Changes and Relevance to Biology - Xu, M.; Deng, Y.; Luck, C.; Sharma, A.; Markelz, A. (APS 2018, 2018)

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Global Picosecond Structural Dynamics of Orange Carotenoid Protein in Photo/Chemical Activated Signaling States - Deng, Y.; Xu, M.; Liu, H.; Blankenship, R.; Markelz, A. (APS 2017 S4.002, 2017)

Orange Carotenoid Protein Picosecond Dynamics Changes with Photo and Chemical Activation - Deng, Y. T.; Xu, M. Y.; Liu, H. J.; Blankenship, R. E.; Markelz, A. G. (Biophysical Journal, 2017)
ISI Document Delivery No.: EW3DS Times Cited: 0 Cited Reference Count: 3 Cited References: King JD, 2014, FEBS LETT, V588, P4561, DOI 10.1016/j.febslet.2014.10.024 Wilson A, 2006, PLANT CELL, V18, P992, DOI 10.1105/tpc.105.040121 Wilson A, 2008, P NATL ACAD SCI USA, V105, P12075, DOI 10.1073/pnas.0804636105 Deng, Yanting Xu, Mengyang Liu, Haijun Blankenship, Robert E. Markelz, Andrea G. 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc Liu, Haijun/0000-0003-0537-0302 14 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Hydration and temperature interdependence of protein picosecond dynamics - Lipps, F.; Levy, S.; Markelz, A. G. (Physical Chemistry Chemical Physics, 2012)
We investigate the nature of the solvent motions giving rise to the rapid temperature dependence of protein picoseconds motions at 220 K, often referred to as the protein dynamical transition. The interdependence of picoseconds dynamics on hydration and temperature is examined using terahertz time domain spectroscopy to measure the complex permittivity in the 0.2-2.0 THz range for myoglobin. Both the real and imaginary parts of the permittivity over the frequency range measured have a strong temperature dependence at >0.27 h (g water per g protein), however the permittivity change is strongest for frequencies <1 THz. The temperature dependence of the real part of the permittivity is not consistent with the relaxational response of the bound water, and may reflect the low frequency protein structural vibrations slaved to the solvent excitations. The hydration necessary to observe the dynamical transition is found to be frequency dependent, with a critical hydration of 0.19 h for frequencies >1 THz, and 0.27 h for frequencies <1 THz. The data are consistent with the dynamical transition solvent fluctuations requiring only clusters of similar to 5 water molecules, whereas the enhancement of lowest frequency motions requires a fully spanning water network.
ISI Document Delivery No.: 928AI Times Cited: 25 Cited Reference Count: 39 Cited References: Bonvicini D, 1998, IEEE T DIELECT EL IN, V5, P33, DOI 10.1109/94.660757 BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 Brovchenko I, 2008, CHEMPHYSCHEM, V9, P2695, DOI 10.1002/cphc.200800662 Chen G, 2008, PHILOS MAG, V88, P3877, DOI 10.1080/14786430802585117 Chen JY, 2005, PHYS REV E, V72, DOI 10.1103/PhysRevE.72.040901 Chen SH, 2006, P NATL ACAD SCI USA, V103, P9012, DOI 10.1073/pnas.0602474103 Ding T, 2011, J PHYS CHEM A, V115, P11559, DOI 10.1021/jp200553d Doster W, 2010, PHYS REV LETT, V104, DOI 10.1103/PhysRevLett.104.098101 DOSTER W, 1989, NATURE, V337, P754, DOI 10.1038/337754a0 Doster W, 2010, BBA-PROTEINS PROTEOM, V1804, P3, DOI 10.1016/j.bbapap.2009.06.019 Ebbinghaus S, 2007, P NATL ACAD SCI USA, V104, P20749, DOI 10.1073/pnas.0709207104 Frauenfelder H, 2003, P NATL ACAD SCI USA, V100, P8615, DOI 10.1073/pnas.1633688100 GASCOYNE PRC, 1977, J CHEM SOC FARAD T 1, V73, P171, DOI 10.1039/f19777300171 GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 HARVEY SC, 1972, J PHYS CHEM-US, V76, P2987, DOI 10.1021/j100665a011 He YF, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.178103 Kauzmann W, 1942, REV MOD PHYS, V14, P0012, DOI 10.1103/RevModPhys.14.12 Khodadadi S, 2010, BBA-PROTEINS PROTEOM, V1804, P15, DOI 10.1016/j.bbapap.2009.05.006 Knab J, 2006, BIOPHYS J, V90, P2576, DOI 10.1529/biophysj.105.069088 Makarov VA, 2000, BIOPHYS J, V79, P2966, DOI 10.1016/S0006-3495(00)76533-7 Markelz AG, 2008, IEEE J SEL TOP QUANT, V14, P180, DOI 10.1109/JSTQE.2007.913424 Markelz AG, 2007, CHEM PHYS LETT, V442, P413, DOI 10.1016/j.cplett.2007.05.080 Oleinikova A, 2005, PHYS REV LETT, V95, DOI 10.1103/PhysRevLett.95.247802 Oleinikova A, 2005, J PHYS CHEM B, V109, P1988, DOI 10.1021/jp045903j Oleinikova A, 2006, MOL PHYS, V104, P3841, DOI 10.1080/00268970601108229 Paciaroni A, 2008, PHILOS MAG, V88, P4071, DOI 10.1080/14786430802464263 Parak FG, 2003, CURR OPIN STRUC BIOL, V13, P552, DOI 10.1016/j.sbi.2003.09.004 Pawlus S, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.108103 Roh JH, 2006, BIOPHYS J, V91, P2573, DOI 10.1529/biophysj.106.082214 Roh JH, 2009, BIOPHYS J, V96, P2755, DOI 10.1016/j.bpj.2008.12.3895 Roh JH, 2005, PHYS REV LETT, V95, DOI 10.1103/PhysRevLett.95.038101 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 Schiro G, 2011, J PHYS CHEM LETT, V2, P2275, DOI 10.1021/jz200797g Shen YC, 2003, APPL PHYS LETT, V82, P2350, DOI 10.1063/1.1565680 Soderholm S, 2000, J RAMAN SPECTROSC, V31, P995, DOI 10.1002/1097-4555(200011)31:11<995::AID-JRS634>3.0.CO;2-L Whitmire SE, 2003, BIOPHYS J, V85, P1269, DOI 10.1016/S0006-3495(03)74562-7 WU Q, 1995, APPL PHYS LETT, V67, P3523, DOI 10.1063/1.114909 Zaccai G, 2000, SCIENCE, V288, P1604, DOI 10.1126/science.288.5471.1604 Zhang CF, 2006, J PHYS CHEM B, V110, P23607, DOI 10.1021/jp063545+ Lipps, Ferdinand Levy, Seth Markelz, A. G. Markelz, Andrea/0000-0003-0443-4319 26 66 Royal soc chemistry Cambridge 1463-9084
Keywords: Chemistry; dielectric-relaxation; fluctuations; inelastic neutron-scattering; lysozyme; myoglobin; percolation; Physics; spectra; spectroscopy; terahertz beams; transition; water

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
ISI Document Delivery No.: 896NY Times Cited: 164 Cited Reference Count: 35 Cited References: Akhmerov AR, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.216404 Alpichshev Z, 2010, PHYS REV LETT, V104, DOI 10.1103/PhysRevLett.104.016401 Analytis JG, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.205407 Bansal N., ARXIV11045709 Benia HM, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.177602 Bianchi M, 2010, NAT COMMUN, V1, DOI 10.1038/ncomms1131 Butch NP, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.241301 Chen J, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.241304 Chen YL, 2009, SCIENCE, V325, P178, DOI 10.1126/science.1173034 Essin AM, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.146805 Eto K, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.195309 Fu L, 2007, PHYS REV B, V76, DOI 10.1103/PhysRevB.76.045302 Fu L, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.096407 Hsieh D, 2008, NATURE, V452, P970, DOI 10.1038/nature06843 Hsieh D, 2009, NATURE, V460, P1101, DOI 10.1038/nature08234 Jenkins GS, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125120 King PDC, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.096802 LaForge AD, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.125120 Lan YP, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.205109 Maciejko J, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.166803 Moore JE, 2007, PHYS REV B, V75, DOI 10.1103/PhysRevB.75.121306 Qi XL, 2008, PHYS REV B, V78, DOI 10.1103/PhysRevB.78.195424 Qu DX, 2010, SCIENCE, V329, P821, DOI 10.1126/science.1189792 Roushan P, 2009, NATURE, V460, P1106, DOI 10.1038/nature08308 Roy R, 2009, PHYS REV B, V79, DOI 10.1103/PhysRevB.79.195322 Steinberg H, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.233101 Sushkov AB, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125110 THOULESS DJ, 1982, PHYS REV LETT, V49, P405, DOI 10.1103/PhysRevLett.49.405 Tkachov G, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.035405 Tse WK, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.161104 Tse WK, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.057401 VONKLITZING K, 1980, PHYS REV LETT, V45, P494, DOI 10.1103/physrevlett.45.494 Xia Y, 2009, NAT PHYS, V5, P398, DOI 10.1038/NPHYS1274 Xiong J., PHYSICA A E IN PRESS Zhang XA, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.245107 Aguilar, R. Valdes Stier, A. V. Liu, W. Bilbro, L. S. George, D. K. Bansal, N. Wu, L. Cerne, J. Markelz, A. G. Oh, S. Armitage, N. P. George, Deepu/J-9882-2014; Aguilar, Rolando Valdes/A-6637-2012; Liu, Wei/H-5999-2012; Wu, Liang/C-8715-2015 George, Deepu/0000-0003-0021-0705; Aguilar, Rolando Valdes/0000-0002-4321-4792; Wu, Liang/0000-0003-1696-7809; Markelz, Andrea/0000-0003-0443-4319 "Institute for Quantum Matter" DOE [DE-FG02-08ER46544]; Gordon and Betty Moore FoundationGordon and Betty Moore Foundation; NSFNational Science Foundation (NSF) [MRI-R2 0959989, DMR-1006078, DMR-0845464]; IAMDN of Rutgers University; ONROffice of Naval Research [N000140910749]; Division Of Materials ResearchNational Science Foundation (NSF)NSF - Directorate for Mathematical & Physical Sciences (MPS) [0845464] Funding Source: National Science Foundation The authors would like to thank H. D. Drew, J. Hancock, Z. Hao, G. S. Jenkins, A. Kuzmenko, A. MacDonald, N. A. Mecholsky, A. J. Pearson, O. Tchernyshyov, W-K. Tse, and Y. Wan for helpful discussions and/or correspondences. Support for the measurements at JHU was provided under the auspices of the "Institute for Quantum Matter" DOE DE-FG02-08ER46544 and the Gordon and Betty Moore Foundation. The work at UB was supported by NSF MRI-R2 0959989 and NSF DMR-1006078. The work at Rutgers was supported by IAMDN of Rutgers University, NSF DMR-0845464 and ONR N000140910749. 166 3 157 Amer physical soc College pk
Keywords: bi2te3; Physics

The role of the protein surface on the local biological water dynamics - Liang, W.; He, Y. F.; George, D.; Markelz, A. G. (Biosensing Ii, 2009)
Protein function is reliant on structural flexibility and this flexibility is slaved to the surrounding solvent. Here we discuss how the exposed surface of the protein influences the solvent dynamics and thereby influences the protein's own structural dynamics. We discuss measurements of the THz absorption of water in the presence of hydrophilic and hydrophobic surfaces.
ISI Document Delivery No.: BVQ85 Times Cited: 0 Cited Reference Count: 12 Cited References: Balu R, 2008, BIOPHYS J, V94, P3217, DOI 10.1529/biophysj.107.105163 Bergner A, 2005, REV SCI INSTRUM, V76, DOI 10.1063/1.1928427 Born B, 2009, J AM CHEM SOC, V131, P3752, DOI 10.1021/ja808997y Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 He YF, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.178103 Heugen U, 2006, P NATL ACAD SCI USA, V103, P12301, DOI 10.1073/pnas.0604897103 Jepsen PU, 2007, OPT EXPRESS, V15, P14717, DOI 10.1364/OE.15.014717 Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g Knab J, 2006, BIOPHYS J, V90, P2576, DOI 10.1529/biophysj.105.069088 THRANE L, 1995, CHEM PHYS LETT, V240, P330, DOI 10.1016/0009-2614(95)00543-D Xu J, 2006, J CHEM PHYS, V124, DOI 10.1063/1.2151267 Yada H, 2008, CHEM PHYS LETT, V464, P166, DOI 10.1016/j.cplett.2008.09.015 Liang, Wei He, Yunfen George, Deepu Markelz, A. G. Proceedings Paper Conference on Biosensing II Aug 04-06, 2009 San Diego, CA Spie George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705; Markelz, Andrea/0000-0003-0443-4319 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x 73970t
Keywords: alanine; dynamics; hydration; lysine; lysozyme; proteins; relaxation; spectroscopy; Terahertz; thz

Ultrafast Carriers Dynamics in GaSb/Mn Random Alloys - Ye, S.; Knab, J.; Chen, J.-Y.; Wang, S.; Cheon, M.; Luo, H.; Markelz, A. G. (Proceedings of the 28th International Conference on the Physics of Semiconductors, 2006)

Terahertz grid frequency doublers - Chiao, Jung-Chih; Markelz, Andrea; Li, Yongjun; Hacker, Jonathan; Crowe, Thomas; Allen, James; Rutledge, David (Proc. Sixth Intl. Symp. Space Terahertz Tech, 1995)

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.
Sherwin, Mark S/Q-4762-2017; Guimaraes, Paulo Sergio Soares/B-6918-2012 Sherwin, Mark S/0000-0002-3869-1893; Guimaraes, Paulo Sergio Soares/0000-0002-0113-2641; Markelz, Andrea/0000-0003-0443-4319 1993 International Conference on Luminescence (ICL 93) Aug 09-13, 1993 Univ connecticut, storrs, ct Univ connecticut; opt soc amer; amer phys soc; ieee, laser & electro opt soc; int union pure & appl phys; int sci fdn; univ connecticut res fdn 3

SPECIFIC-HEAT MEASUREMENTS ON SUPERCONDUCTING BI-CA-SR-CU AND TL-CA-BA-CU OXIDES - ABSENCE OF A LINEAR TERM IN THE SPECIFIC-HEAT OF BI-CA-SR-CU OXIDES - Fisher, R. A.; Kim, S.; Lacy, S. E.; Phillips, N. E.; Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Ginley, D. S. (Physical Review B, 1988)
Fisher, Robert Anthony/H-6779-2019 Markelz, Andrea/0000-0003-0443-4319 B 68